A brief idea on application of the Quasi Random Model to study the propagation of a laser beam through water vapour. - Bhuyan, Surajit (International Journal of Scientific Research and Management (IJSRM), 2015)
Interaction of a Ti: sapphire laser beam of wavelength 9335 Å with the near-infrared absorption lines of  using the quasi-random model of molecular band absorption. Values of¾water vapour is studied  , are obtained for three different absorber thickness.1-transmittance, averaged over intervals of 0.1 cm From these values, intensities of the high-resolution absorption lines of water vapour are simulated in the 1-vicinity of 10712 cm